SUBSURFACE MODELING BASED ON GRAVITY DATA DANAU RANAU GEOTHERMAL FIELD, LAMPUNG AND SOUTH SUMATERA, INDONESIA - Sari Sandjaya, Arum
Lampung is one of the provinces in Sumatera with large area and one of the provinces that lacks electricity supply. This can hinder regional progress. Therefore, alternative energy is needed that can replace fossil energy as power plants, that is geothermal energy. Geothermal potential is around Mount Seminung which is a stratovolcano and the edge of Lake Ranau. This research was conducted using the gravity method. In this study, gravity measurement data was used by the PSDMBP team in 2004. Then, plotting using the krigging method to obtain a complete Bouguer anomaly and topohgraphy map. Then, regional and residual anomalies are separated using moving average and second order polynomial trend surface interpolation method. Of the two methods, residual anomaly from the moving average was chosen because it produces a anomaly map is more suitable with geological information. From forward modelling 2.5 D, the presence of high anomaly is estimated as magma intrusion with a density 2.92 gr/cc. The magma intrusion to be a heat source of hot water manifestations. The reservoir in Lake Ranau area in Ranau pyroclastic lava with a density of 2.50 gr/cc. Seminung 1 lava become the caprock in Lake Ranau area.